Implied Author in Philosophical Novels - Senkāne, Olga (Respectus Philologicus, 2014)
The present article falls within a number of papers about research on specification of philosophical novels. The aim of this article is to analyze author’s function as a narrative category in classical philosophical novels (Franz Kafka "The Trial" (1925) ”The Castle”(1926), Jean-Paul Sartre "Nausea" (1938), Hermann Hesse "The Glass Bead Game" (1943), Albert Camus ”The Plague” (1947)) and a novel of Latvian prose writer Ilze Šķipsna „Neapsolītās zemes” [Un-Promised Lands](1970)). The analysis is based on theoretical ideas of structural narratologists Gerard Genette, William Labov, Seymuor Chatman, Wolf Schmid, as well as philosophers Edmund Husserl, Jean-Paul Sartre, Paul Ricouer and semioticians Yuri Lotman (Юрий Лотман) and Umberto Eco. The real author can ”enter” the text only indirectly—as an image, with the help of the storyteller, and the way how this ”entry” happens is determined by the narration of the real author or narrative (communication) skills of the author. Thus, the author and implied author are functionally different concepts: author as a real person develops the concept idea, his intention is to define the concept under his original vision; narrator, in its turn, communicates with the reader, representing the concept, and his aim is to select appropriate means of communication with regard to reader’s perceptual abilities.